2016
DOI: 10.1042/bcj20160015
|View full text |Cite
|
Sign up to set email alerts
|

Prestin and the good vibrations

Abstract: In a recent paper published in the Biochemical Journal, Lolli et al. presented evidence that the C-terminal STAS (sulfate transporter and anti-sigma factor antagonist) domain of the motor protein prestin possesses an anion-binding site. This discovery might shed light on an aspect of the function of this mysterious and fascinating protein that is crucial for the human hearing system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…The role of the STAS domain in these SLC26/SulP has not been fully explored, but it has been suggested to be important for targeting proteins to the membrane ( Sharma et al., 2011 ; Compton et al., 2014 ). However, recent work has demonstrated that the STAS domain does not play a direct role in protein targeting in bacteria, but instead is required for protein stabilization and functionality ( Birke and Javelle, 2016 ; Lolli et al., 2016 ). In mammals, such as humans, SLC26 transporters play a diverse and critical role as anion exchangers, with three known mutations that can lead to early onset hereditary diseases: chondrodysplasias, chloride diarrhea, and deafness ( Compton et al., 2011 ; Alper and Sharma, 2013 ; Compton et al., 2014 ).…”
Section: Stas Domains As Part Of Slc26/sulp Familymentioning
confidence: 99%
“…The role of the STAS domain in these SLC26/SulP has not been fully explored, but it has been suggested to be important for targeting proteins to the membrane ( Sharma et al., 2011 ; Compton et al., 2014 ). However, recent work has demonstrated that the STAS domain does not play a direct role in protein targeting in bacteria, but instead is required for protein stabilization and functionality ( Birke and Javelle, 2016 ; Lolli et al., 2016 ). In mammals, such as humans, SLC26 transporters play a diverse and critical role as anion exchangers, with three known mutations that can lead to early onset hereditary diseases: chondrodysplasias, chloride diarrhea, and deafness ( Compton et al., 2011 ; Alper and Sharma, 2013 ; Compton et al., 2014 ).…”
Section: Stas Domains As Part Of Slc26/sulp Familymentioning
confidence: 99%